Uncovering the drivers of employee retention in hospitality industry in Klang Valley - Kok, Chien Liang (2023)
The aim of this research is to investigate the factors influencing employee retention in the hospitality industry within Klang Valley, specifically focusing on work-life balance, work environment, employee compensation, career opportunities and employee empowerment.